Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1515/lpts-2016-0034
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Nanotechnologies and Advanced Materials Industry in Science and Entrepreneurship: Socioeconomic and Technical Indicators. A Case Study of Latvia (Part Two)

Abstract: Part two of the in-depth scientific study clarifies the significant social and technical indicators of the development of nano-field at the macro, micro, and meso development levels of the economic environment in Latvia in the framework of the given theme. The analytical assessment of numerical change in socioeconomic and technical factors clearly demonstrates the interaction of nano-field with the development of science and manufacture, as found out in the study. The identified indicators are proposed to use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
(13 reference statements)
1
1
0
Order By: Relevance
“…In accordance with the above-mentioned topicality and the continuation of the present study, which follows and correlates with the in-depth analysis of the previous two studies [2], [3], the development of the nano-field can also be identified and revealed from the perspective of scientific indicators. With regard to the structure of the research on nanotechnologies and advanced materials industry in science and entrepreneurship, it should be noted that the research will reveal crucial scientific indicators of the development of the nano-field at the macro, micro, and meso development levels of economic environment in Latvia.…”
Section: Introductionsupporting
confidence: 89%
“…In accordance with the above-mentioned topicality and the continuation of the present study, which follows and correlates with the in-depth analysis of the previous two studies [2], [3], the development of the nano-field can also be identified and revealed from the perspective of scientific indicators. With regard to the structure of the research on nanotechnologies and advanced materials industry in science and entrepreneurship, it should be noted that the research will reveal crucial scientific indicators of the development of the nano-field at the macro, micro, and meso development levels of economic environment in Latvia.…”
Section: Introductionsupporting
confidence: 89%
“…One of the novelties in green building certification is the green building assessment tool integrated with BIM that can help the design team in the generation of necessary documentation to obtain green building certification [11]. However, socio-economic aspects still are important as they indicate well-being of society [10], and socio-economic aspects are especially important for green building construction and realisation opportunities. Green building certification is an indicator that can show building performance by many parameters, and the number of certified green buildings is increasing worldwide.…”
Section: Overview Of Theoretical Aspects and International Experiencementioning
confidence: 99%